Performance Management in Higher Education: Institutional, Operational, and Value Dimensions at Gorontalo State University - Alexander H. Badjuka; Asna Aneta; Zuchri Abdussamad; Yanti Aneta (Journal Public Policy, 2026)
This study examines performance management in higher education by developing an integrative framework that bridges institutional governance, operational systems, and value orientation within the implementation of Indonesia’s Government Agency Performance Accountability System (SAKIP). Focusing on Gorontalo State University, the research addresses a critical gap in performance management studies that often treat institutional, operational, and value dimensions separately without integrating local governance context and organizational culture.  Using a qualitative case study approach, this research employs document analysis, institutional performance reports, regulatory reviews, and in-depth analytical triangulation. The analysis is guided by three analytical dimensions: institutional (commitment, legitimacy, digital leadership), operational (planning, measurement, reporting, and evaluation), and value orientation (effectiveness, efficiency, accountability). The findings reveal that performance improvement at Gorontalo State University was driven by strengthened leadership commitment, digital governance initiatives, and alignment of strategic planning with Key Performance Indicators (IKU). However, institutional legitimacy through internal regulations and integrated performance information systems remains incomplete. At the value level, organizational agility and accountability culture require further consolidation to ensure sustainable governance transformation. The study introduces the "Lekko" model as a novel performance management framework, enhancing performance through legality, electronic governance, concern, and collaboration. The research contributes theoretically by expanding performance management literature in higher education governance and practically by offering a replicable adaptive framework for public universities in developing countries undergoing bureaucratic reform and digital transformation.